Improving the Studentsâ€™ Vocabulary Mastery by Using Duolingo And Cake Applications - Ginting, Mayasari br; Sinambela, Erika; Manurung, Lastri Wahyuni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The study concentrated on using the Cake and Duolingo apps to help students in the Rebecca Course and Center develop their vocabulary. The purpose of this study was to answer the following question: "Does using the Cake and Duolingo apps improve students' vocabulary, and which app is more significant at the Rebekka Course and Center?" The main goal of the study was to determine which application is more relevant at the Rebekka Course and Center and whether the Duolingo and Cake programs help students' vocabulary. This research used Classroom Action Research (CAR). The subject of the research was Bremen and Frankfurt class and the total of them was 30. This research used two cycles namely cycle I and cycle II and every cycle had four steps namely planning, implementing, observing and reflecting. The observation was analyzed qualitatively, the test was analyzed quantitatively. In cycle l using the Duolingo application the students mean score was 71.3, while mean score of the students' in cycle II was 85. It can be concluded that the Duolingo application improved the students' ability in vocabulary students learning outcomes improve. In cycle l using the Cake application the students mean score was 67.3, while mean score of the students' in cycle II was 83.3. It can be concluded that the Cake application improved the students' ability in vocabulary students learning outcomes improve. teaching vocabulary using Duolingo was more significant in increasing students' vocabulary than the Cake application. This is proven by the average score in the second cycle for the class taught by Duolingo, which was 85. Meanwhile, the class taught with the Cake application had an average score of 83.3.Â Keywords: Improve vocabulary, Duolingo application, Cake Application